Treatment of chronic Osteomyelitis with vascularized bone flaps in one-stage-procedure - Ciclamini, Davide; Antonini, Andrea; Tos, Pierluigi; Crosio, Alessandro; Piccato, Alice; Battiston, Bruno (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
Background Chronic osteomyelitis is a long-standing infection of the bone. Treatment is often combined, using antibiotics and surgery (with radical debridement and secondary or concomitant reconstruction). One-stage management is an alternative approach, with few reported cases in literature.Patients/Material and methods We carried out an observational retrospective multicenter study to evaluate the results of one-stage reconstructions with vascularized bone flaps. We assessed bone and infection healing in 14 cases, with a mean follow-up of 63.6 months. Results: Bone union was obtained in 10 cases (71.4 %) in a mean period of 7.9 months. Nonunion occurred in 4 cases (28.6 %), 2 of them with infection persistence. Bone nonunion risk increases in polymicrobial infections (p = 0.0269) and in compromised hosts (p = 0.0110). Infection healing was achieved in 11 cases (78.6 %). Fistula recurred in 3 cases of forearm osteomyelitis (21.4 %) in 10 months on average. Infection recurrence is associated with polymicrobial infections (p = 0.0378) and is higher in internal fixation and compromised hosts with no statistically significant relation.Conclusions One-stage surgical treatment seems to be an effective approach in selected patients, in particular when an important impairment of local soft tissue and bone exposure are present, and immediate bone coverage with vascularized soft tissue is needed. Most complications occurred in compromised hosts and in patients with polymicrobial cultures. Further research, with comparison between one and two-stage procedures, is needed in order to strengthen the level of evidence.
Keywords: Chronic osteomyelitis; one-stage treatment; one-stage reconstruction; vascularized bone flap